Formulation and Physicochemical Evaluation of Joshanda (Decoction) Munzije Balgham as Granules - Shah, Sabeena; Hamiduddin; Nagraj (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Joshanda (decoction) is an effective dosage form in Unani System of Medicine but its unpalatable taste and preparation creates difficulty in patient compliance. Joshanda when freshly prepared has a very short shelf life. Thus, the modified dosage form like granules can fulfill these drawbacks and withstand the need of contemporary life style as a ready to use and in portable form. In this study, an attempt was made to modify Joshanda Munzjie Balgham (JMB) into contemporary granule dosage form with the help of suitable permissible excipients. Materials and Methods JMB. was prepared by classical method and dried in Rotary evaporator followed by complete drying on water-bath. The extract was then mixed with required excipients to form the granules by wet granulation technique. The modified granules and JMB were subjected to various physico-chemical analysis, qualitative and quantitative estimation of phytoconstituents, GCMS, Microbial count, LCMS and HPTLC. Joshanda Munzije Balgham Granules (JMBG) were also subjected to stability study with accelerated conditions of temperature 40±2°C and relative humidity 75±5°C for three months. Results From one dose of JMB, 28% extract yield percentage was obtained which was successfully converted into fast dissolving JMBG with various excipients. Qualitative analysis of granules confirmed the presence of various phytoconstituents. Quantitative estimation by spectrophotometric method showed the presence of total concentration of Phenols, Tannins, Glycosides, Flavonoids, and Alkaloids as 157.51, 22.35, 2.25, 98.68 and 195.5 μg/mL respectively. GCMS data displayed total 31 peaks in JMB, 8 in JMBG and 8 in JMBG (3rd month). LCMS data for JMBG displayed 28 constituent peaks. HPTLC fingerprinting carried out in two mobile phases reported the highest number of peaks in in toluene; ethyl acetate: formic acid (5:4:1). JMB Granules were found to achieve shelf life of one year on set parameters. The chemical constituents found by qualitative and quantitative analysis and chromatography of JMB and JMBG were comparative. Conclusion This work can help in improving the shortcomings of traditional Munzije Balgham Joshanda to some extent and make it portable, palatable and increases its shelf life.
Keywords: Decoction; Fast dissolving Granules; Joshanda Munzije Balgham; Wet Granulation